2012
DOI: 10.1373/clinchem.2011.179903
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Cardiac Troponin I and T Measured with Sensitive Assays in Emergency Department Patients with Noncardiac Chest Pain

Abstract: BACKGROUND: New-generation high-sensitivity assays for cardiac troponin have lower detection limits and less imprecision than earlier assays. Reference 99th-percentile cutoff values for these new assays are also lower, leading to higher frequencies of positive test results. When cardiac troponin concentrations are minimally increased, serial testing allows discrimination of myocardial infarction from other causes of increased cardiac troponin. We assessed various measures of short-term variation, including abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 16 publications
3
22
0
Order By: Relevance
“…Another reason for the low CVi values in the current study is that the adjustment of the data to establish a steady state provides lower values compared to the noncorrected data used in other studies. However, the 90-min asymmetric RCV value (i.e., including CVa and CVi, and adding the ␤ value corresponding to the systematic decline) was similar to the RCV values found in some studies (17,21,23 ) and lower than those found in others (16,18,19,22 ).…”
Section: Discussionsupporting
confidence: 85%
“…Another reason for the low CVi values in the current study is that the adjustment of the data to establish a steady state provides lower values compared to the noncorrected data used in other studies. However, the 90-min asymmetric RCV value (i.e., including CVa and CVi, and adding the ␤ value corresponding to the systematic decline) was similar to the RCV values found in some studies (17,21,23 ) and lower than those found in others (16,18,19,22 ).…”
Section: Discussionsupporting
confidence: 85%
“…Studies of healthy individuals so far have shown the short-and long-term biological variations of cardiac troponin to be in the range of 3%-48% and 3%-117%, respectively; the short-term RCV has ranged from 44% to 113% and the short-term log-normal RCV for rising concentrations from 45% to 90% (12-15, 26, 27, 29 ). Similarly, in a recent study of patients presenting with chest pain in an emergency department, excluding patients with known stable angina, the individual variation was similar to that in healthy controls at 11% for cTnI and 18% for cTnT (28 ). In another recent study of patients with stable cardiovascular disease, the long-term CV i of cTnI was 28%, and log-normal RCV for rising and falling concentrations 98% and Ϫ50%, respectively, very similar to the long-term results in the present study (29 ).…”
Section: Discussionmentioning
confidence: 54%
“…Troponin T responded the same way with the hs-cTnT assay [27]. The short-term RCVs measured by ARCHITECT (Abbott), Vista (Siemens), Access 2 (Beckmann) and Centaur (Siemens) assays are around the 50% range [27]. The RCV of hs-cTnT varies in the 38-58% range, depending on the study [27,28].…”
Section: When Does a Change In Hs-ctn Become Significant?mentioning
confidence: 80%
“…Wu et al studied short-term (within-day) and long-term (between-day) biological variation in hs-cTnI (Singulex ® assay) in healthy subjects [26], and found that cTnI demonstrates low intraindividual variation, but high interindividual variation -in other words, cTnI shows high-individuality. Troponin T responded the same way with the hs-cTnT assay [27]. The short-term RCVs measured by ARCHITECT (Abbott), Vista (Siemens), Access 2 (Beckmann) and Centaur (Siemens) assays are around the 50% range [27].…”
Section: When Does a Change In Hs-ctn Become Significant?mentioning
confidence: 80%
See 1 more Smart Citation